Pengertian dan urgensi mempelajari qira’at al-quran - Jannah, Miftahul (Maliki Interdisciplinary Journal, 2025)
Qirā’at is a crucial discipline in Qur’anic studies that deals with the variations in the recitation of Qur’anic verses attributed to different qirā’ah imams. Etymologically, qirā’at means “reading,” and terminologically, it refers to specific recitation methods supported by an authentic chain of transmission (sanad) reaching back to the Prophet Muhammad (PBUH). A valid qirā’ah must meet three essential criteria: alignment with classical Arabic dialects, conformity with the Uthmani script, and a continuous, reliable sanad. Any qirā’ah that fails to meet these standards is classified as weak, deviant, or fabricated. Ibn al-Jazari categorized qirā’at into five types: mutawātir, mashhūr, āḥād, shādh, and mawḍū‘. The diversity in qirā’ah dates back to the Prophet’s time and is rooted in divine mercy through the concept of “seven aḥruf” (dialects or forms). Scholars have proposed various interpretations of this concept, including dialectical, grammatical, and linguistic variations. This study underscores that the differences in qirā’at should be viewed as a valuable aspect of Islamic heritage, rather than a cause for division.